Influence of the perception of biological or non-biological motion on movement execution - Bouquet, C. A.; Gaurier, V.; Shipley, T.; Toussaint, L.; Blandin, Y. (Journal of Sports Sciences, 2007)
The perception of a human actor performing movements may involve processes related to action execution. This resonance of the motor system may support observational learning and imitation, and could also explain the fact that observers'/actors' movements are disturbed by the observation of a human model making different movements (Kilner et al., 2003). In this study, we tried to specify what information available in the model's behaviour triggers this influence on an observer's behaviour. In two experiments, we had participants make horizontal or vertical arm movements while observing similar movements. In the first experiment, the observers' pattern of behaviour was affected by the observation of a human model making incongruent movements. In the second experiment, similar results were obtained with participants observing a moving dot depicting either biological or non-biological motion. Movement execution was affected differentially by biological and non-biological motion observation. These results show that an observer's behaviour is sensitive to information available in biological motion.